COMPARATIVE ANALYSIS OF AI AND HUMAN TRANSLATION - Kuvondikova Shaydo Toʻlqinovna (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: The rapid development of artificial intelligence technologies has significantly transformed the field of translation studies. Among modern AI-based systems, ChatGPT has become one of the most widely used tools for automatic text generation and translation. This thesis examines the comparative analysis of ChatGPT translation and human translation, focusing on their strengths, weaknesses, and practical effectiveness in English-Uzbek translation processes. The study investigates translation quality in terms of grammatical accuracy, semantic equivalence, contextual understanding, cultural adaptation, and stylistic appropriateness. Comparative and descriptive research methods are applied to analyze different translated texts produced by ChatGPT and professional human translators. The findings demonstrate that ChatGPT provides fast, accessible, and grammatically accurate translations for general and informational texts. However, the research also reveals that AI-generated translations may contain semantic inaccuracies, literal interpretations, and cultural misunderstandings, especially in idiomatic expressions, literary texts, and culturally sensitive materials. Human translators, on the other hand, possess contextual awareness, emotional understanding, and cultural competence that allow them to produce more natural and communicatively effective translations. The study concludes that ChatGPT should be considered an assisting tool rather than a complete replacement for professional translators. The integration of artificial intelligence with human expertise may improve translation efficiency and quality in the future.